A Framework for Creating and Using Teaching Philosophy Statements to Guide Reflective and Inclusive Instruction - Steven D. Taff (Journal of Occupational Therapy Education, 2023)
A teaching philosophy statement (TPS) is a brief, deeply personal narrative that gives insight into an educator’s perspective on the teaching enterprise. A TPS is typically comprised of a reflection on the educator’s values and beliefs, a description of what happens during the learning process, and statements about how teachers and learners ideally interact. Use of a TPS clarifies the bridge between theory/philosophy and practice which strengthens education as an interactive phenomenon and in so doing evokes an ethical purpose for the teaching-learning dynamic. This article describes the theoretical underpinnings of, and process for, an innovative framework occupational therapy educators can use to construct, implement, and evaluate a TPS based upon the beliefs, actions, and anticipated outcomes of their teaching. Creating and consistently using a TPS is an essential faculty development activity, one that nudges educators to be more deeply reflective and capable of building inclusive learning environments where every student is engaged and feels welcome as part of a community of learners.